10.1371/journal.pmed.0020297 (CrossRef Listing of Deleted DOIs, 2000)
Measles remains a significant cause of childhood mortality globally. Despite effective vaccines, the World Health Organisation reported an estimated 10.3 million measles cases worldwide in 2023, a 20% increase from 2022, primarily due to insufficient vaccination coverage. Madagascar faced a major measles epidemic in 2018-2019, prompting vaccination efforts. A convergent parallel mixed-methods design was utilised, wherein quantitative household surveys and semi-structured qualitative interviews were conducted concurrently. Data were integrated during the interpretation phase to triangulate statistical determinants with contextual stakeholder insights regarding the performance of the October 2024 measles vaccination campaign and its determinants across different geographical areas. This retrospective, cross-sectional Post-Measles Campaign Evaluation (PMCE) was conducted from December 2024 to April 2025, following the October 2024 campaign. It involved quantitative household surveys and qualitative interviews in all 23 regions of Madagascar, targeting children aged 9-59 months and their caregivers. A two-stage stratified random sampling approach distinguished large cities, landlocked, and intermediate districts. Multivariate logistic regressions were performed to identify geographical, socio-demographic, economic, and cultural determinants of post-campaign vaccination coverage. The study revealed a national post-campaign vaccination coverage of 75.3% in 2024, a notable 10-point increase from 65.3% in 2022. However, significant geographical disparities persisted (p-value = 0.0233), with lower coverage in large cities (63.2%) compared to landlocked (78.4%) and intermediate (76.2%) districts. Multivariate analysis showed that residing in a large city significantly reduced post-campaign vaccination coverage (OR adjusted = 0.25; p = 0.010). Conversely, male child gender (OR adjusted = 1.33; p = 0.040), birth in a health facility (OR adjusted = 1.38; p = 0.046), possession of a birth certificate (OR adjusted = 2.30; p < 0.001), having a Christian caregiver (OR adjusted = 1.92; p < 0.001), or a housewife caregiver (OR adjusted = 1.97; p = 0.015) were associated significantly higher post-campaign vaccination coverage. The identified statistical determinants, notably the lower coverage among urban residents (ORa = 0.25), were contextualised using qualitative data, which highlighted that 'urban vaccine hesitancy' is exacerbated by metropolitan misinformation and the misconception that previously vaccinated children did not require campaign doses. While Madagascar's post-campaign measles vaccination coverage shows encouraging progress, significant geographical and socio-demographic disparities underscore the need for tailored strategies. Addressing urban-specific challenges, strengthening communication, improving logistics, and leveraging community engagement are crucial for achieving equitable immunisation coverage and advancing towards measles elimination targets.